Dealing with crisis: Early childhood teachers perceived role in supporting children - Figueiredo, Maria Pacheco (2016)
The study explored how two experienced early childhood teachers support children dealing with crisis in their home environment, namely divorce, domestic violence and imprisonment of parents. The focus was on the relationship between the educational environment (organisation of space, time and relationships in an ecological perspective) and children's emotional well-being. This study builds on studies in Portugal about emotional well-being (Portugal & Laevers, 2010) and about the impact on children from imprisoned parents (Afonso, 2005, Kominsky, Pinto & Miyashiro, 2005, Tavares, 2011), domestic violence (Batista, 2014, Lisboa et al., 2002, Ribeiro, 2010) and divorce (Martons, 2010, Rego, 2008). The theoretical framework was weaved with Laevers (2004) concepts of emotional well-being and involvement and Siraj-Blatchford (2002) and Figueiredo (2013) perspective of pedagogy as including different dimensions of which the educational environment is essential. In-depth interviews with both teachers and some observations of their classroom dynamics were analysed for emerging cross themes in this qualitative study. Anonymity was preserved throughout the study by the use of codes. The study was presented to the teachers and questions were presented in advance. Both teachers expressed preference for adapting existing pedagogical tools (e.g. the classroom diary) and the daily dynamic to support children instead of using special interventions. Domestic violence was seen as the most problematic situation for its repercussions. Attention to emotional well-being, a strong relationship with the child and the families was highlighted. Pedagogy was described as answering different challenges, with a strong emphasis on children's participation. Thematising teachers' pedagogical knowledge is important.